(untitled) (Third Sector Social Economic Review, 2023)
The developments in information and communication technologies and the emergence of many new areas of innovation brought about by digital transformation have led to the discussion of the education carried out in higher education systems. This discussion is addressed under the concept of “Future Professions”. The purpose of this study is to examine the goals of the Higher Education Council’s ""Future Professions Project"" for the Turkish higher education system, its strategic road map and its interaction with international plans, and to examine its reflections specifically on accounting education. The study was conducted with content analysis, one of the qualitative research techniques. In the research, environmental data and data on the processes carried out were collected through the examination of documents. Considering the effects of the transformation on accounting education, the study proposes an application that aims to support traditional accounting education.